Suzhi Education and General Education in China. (June 2020) - Pang, Haishao; Cheng, Meiling; Yu, Jing; Wu, Jingjing
Purpose: Since the 1980s, suzhi has become a core word in contemporary China. Suzhi education as an education philosophy full of Chinese characteristics has been well known in China for generations. Particularly since 1995, culture-oriented quality education as an anchor and starting point of suzhi education implementation in universities, which integrates with general education and liberal education from Western concepts, triggered great changes in Chinese universities. This article aims to review the concepts of suzhi education, general education, and their practice in China. Design/Approach/Methods: This study is based on historical developments of suzhi education and general education, research literature, and some typical practice cases. Findings: The analysis finds that suzhi education and general education have consistent goals. Their connotations in China can be understood in three aspects: philosophy, education content, and cultivation mode. They caused three great practices in universities, including general education courses, extracurricular suzhi education activities, and reforms on talent cultivation modes. Originality/Value: This article clarifies the localized understanding of suzhi education and general education in three aspects and outlines the overall reforms around suzhi education and general education in Chinese higher education.